Penghargaan "Sang Model Terbaik" Jatuh Pada...? Prediksi Kesulitan Keuangan pada Sektor BUMN Konstruksi - Risma Setya Ardani; Resi Ariyasa Qadri (Journal of Applied Business Administration, 2022)
This research seeks to accomplish two goals: to identify a statistical difference between the three financial distress models—Altman, Zmijewski, and Springate—and to describe which model proves to be the "Most-Valuable-Predictor" in terms of the accuracy with which it can predict the insolvency conditions of state-owned enterprises in Indonesia's construction industry. In this study, the purposive sampling approach was used to select the study's objects. With the aid of documentation techniques, financial data samples were gathered and put through the test of the difference analysis. This paper found a significant difference between the calculations of Altman, Zmijewski, and Springate models in predicting the financial difficulty in the SOE’s construction sector. The most accurate forecast for the industry's financial problems came from the Zmijewski model. The most influential contribution of this study is that it helps investors understand the financial risks before making an investment in the construction industry.